PENGARUH LINGKUNGAN KERJA, PELATIHAN KERJA, DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS GURU PADA SMK ISLAMIC CENTER BERBASIS PONDOK PESANTREN SULAWESI TENGAH - Muhammad J Wartabone (UNES Law Review, 2023)
This study aims to determine the work environment, job training, and work discipline on teacher productivity. The object of this research is Islamic Center Vocational School Teachers based on Central Sulawesi Islamic Boarding Schools engaged in education. The variables used in this study as independent variables are work environment, job training, and work discipline and the dependent variable is teacher productivity. This type of research is descriptive quantitative. This study used a sample of 62 respondents, the data collection technique was a questionnaire (questionnaire). Analysis of the data used is the validity test, reliability test and hypothesis testing. The data were analyzed using multiple regression methods. Then tested by t-test and F-test with a confidence level of 5 percent. As a requirement analysis test, data analysis techniques, and hypothesis testing used is SPSS 25 analysis.